Comparative study of the composition and genetic diversity of the picoeukaryote community in a Chinese aquaculture area and an open sea area. (1st March 2016) - Song, Xue; Xu, Zhimeng; Liu, Qian; Li, Yan; Ma, Yu; Wang, Jian; Sun, Mengran; Shao, Hongbing; Sun, Hui; Malin, Gill; Jiang, Yong; Wang, Min
Abstract : Picoeukaryotes (<2–3 μm) perform key roles for the functioning of marine ecosystems, but little is known regarding the composition and diversity of picoeukaryotes in aquaculture areas. In this study, the Illumina MiSeq platform was used for sequencing the V4 variable region within the 18S rDNA gene to analyse genetic diversity and relative abundance of picoeukaryotic communities in the Qinhuangdao scallop cultivation area of the Bohai Sea. The community was dominated by three super groups, the alveolates (54%), stramenopiles (41%) and chlorophytes (3%), and three groups, dinoflagellates (54%), pelagomonadales (40%) and prasinophytes (3%). Furthermore, a contrasting station with open water away from the eutrophic aquaculture area was chosen. The communities collected from the two stations exhibited significant differences, with higher diversity in the aquaculture area. These results provide the first snapshot of the picoeukaryotic diversity in surface waters of the Qinhuangdao scallop cultivation area, and basic data for future studies on picoeukaryote community in an aquaculture region.